(untitled) (Al-Academy, 2024)
This research is concerned with studying the Aesthetics of design adaptation in the Ornaments of the Prophet’s kiswah. It also aims to provide the recipient with a wider scope to learn about the most important representations of design adaptation in terms of decorations, colors, styles, as well as technique and implementation. Conducted on the Prophet’s kiswah, the research included four chapters. The first chapter included the research problem, which was represented by the following question: What are the representations of design adaptation in the decorations of the Prophet’s kiswah? The researcher limits the goal of the research, which is: revealing the representations of design adaptation in the decorations of the Prophet’s kiswah. The second chapter (theoretical framework) included a topic: Design adaptation between meaning and function. The third chapter included research procedures and relied on the descriptive approach. The research sample was selected according to the research tool represented by the analysis form, the validity of which was confirmed by a group of specialists in this field. As for the fourth chapter It included presenting the results, recommendations and proposals. As well as a list of sources.